ANALISIS PENDAPATAN ASLI DAERAH KOTA BANDAR LAMPUNG TAHUN 2011-2015 - Yohanes P Kumagaya; Yessikha Herminia Maysita (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2018)
Local original income is an income that has an important role for the stability of development ofa region starting from the economy, the infrastructure, the provision of services to the community andothers. In financing local household affairs, local governments should be able to maximize sources oflocal revenue, one of the most important is derived from local taxes. This research is a replication anddevelopment of research conducted by Isfatul Fauziah et al. In 2014 with the object of research in theOffice of Revenue Management of Finance and Assets District of Malang. The aim of this study is todetermine the level of effectiveness and the level of contribution of each type of local tax on localoriginal income in the city of Bandar Lampung.From the analysis, it is known that in the period of five years the type of tax which has highestincome effectiveness rate is derived from non-metal mineral and rock taxes of 124.17%. As for thelowest level of effectiveness of revenue comes from parking taxes with a percentage of 47.2%. Whilethe contribution of local tax to the highest revenue of the region is from street lighting tax withpercentage of 18.36% and the lowest contribution comes from non metallic mineral and rock taxes withpercentage of 0.24%.